2016
DOI: 10.3788/col201614.030601
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analyzing the temperature sensitivity of radiation-induced attenuation in a Ge-P co-doped fiber

Abstract: A model for the temperature sensitivity of radiation-induced attenuation (RIA) is investigated. The RIA spectra in a germanium (Ge) and phosphorous (P) co-doped fiber ranging from 825 to 1600 nm at different temperatures are measured and decomposed according to the configurational coordinate model. It is found that there is a linear relationship between the parameters of the color center absorption band and temperature. The model is verified at 850, 1310, and 1550 nm by both simulation and experiment. This wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[21] In Ref. [17], it was found that there was a linear relationship between the parameters of color center absorption band and temperature. The fitting formula of the Gaussian band can be expressed as…”
Section: Modeling Of the Optical Fiber Attenuation Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…[21] In Ref. [17], it was found that there was a linear relationship between the parameters of color center absorption band and temperature. The fitting formula of the Gaussian band can be expressed as…”
Section: Modeling Of the Optical Fiber Attenuation Spectrummentioning
confidence: 99%
“…The formula for the temperature sensitivity of the RIA in the Ge/P co-doped fiber is shown in Ref. [17].…”
Section: Modeling Of the Optical Fiber Attenuation Spectrummentioning
confidence: 99%
See 1 more Smart Citation